2020
DOI: 10.1111/jcpe.13353
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mid‐buccal gingival recessions in NHANES according to the 2018 World Workshop Classification System

Abstract: Aim There are no nationally representative epidemiological studies available reporting on the different recession types according to the 2018 classification system or focusing on the aesthetic zone. The aims of this cross‐sectional study were (a) to provide estimates on the prevalence, severity and extent of mid‐buccal GRs according to the 2018 classification and (b) to identify their risk indicators in the adult U.S. population from the NHANES database. Materials and Methods Data from 10,676 subjects, represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 40 publications
4
68
1
3
Order By: Relevance
“…This finding may be explained by the higher number of teeth present for longer periods of time in the mouths, when compared with implants. However, when comparing the patient‐level prevalence of buccal PISTD in implants without peri‐implantitis with the one of RT1 gingival recessions ≧1 mm, they appear to be similar (10–15%), suggesting a comparable manifestation of these two apparently similar conditions (Romandini et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be explained by the higher number of teeth present for longer periods of time in the mouths, when compared with implants. However, when comparing the patient‐level prevalence of buccal PISTD in implants without peri‐implantitis with the one of RT1 gingival recessions ≧1 mm, they appear to be similar (10–15%), suggesting a comparable manifestation of these two apparently similar conditions (Romandini et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Gingival recession (GR) has been defined as the apical shift of the gingival margin in respect to the cementoenamel junction with concomitant exposure of the root surface in the oral cavity [1]. Several etiological factors such as tissue phenotype, gingival thickness, brushing technique, non-carious and carious cervical lesions, and periodontal predisposition were identified for this condition [2], which may account for its relatively high incidence in the population (45%) [3][4][5]. Root coverage procedures have been shown to be effective in treating single and multiple GRs [6][7][8], with large evidence supporting the superiority of coronally advanced flap (CAF) combined with connective tissue graft Medicina 2021, 57, 144 2 of 20 (CTG) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The area of the KG may influence the mechanical stability of the soft tissue, such as susceptibility to the recession. However, epidemiologic studies demonstrated heterogeneous findings [23][24][25].…”
Section: Discussionmentioning
confidence: 99%